OPTIMALISASI KUALITAS TELUR PUYUH MELALUI KOMBINASI SUPLEMENTASI TEPUNG DAUN KELOR (Moringa oleifera) DAN SARI BELIMBING WULUH (Averrhoa bilimbi L.) SEBAGAI FEED ADDITIVE ALAMI: OPTIMIZATION OF QUAIL EGG QUALITY THROUGH COMBINED SUPPLEMENTATION OF MORINGA LEAF POWDER (Moringa oleifera) AND BILIMBI FRUIT EXTRACT (Averrhoa bilimbi L.) AS NATURAL FEED ADDITIVES - Fadilla Meidita; Nadia Rahma; Dwi Ananta (Universitas Boyolali, 2026)
Quail are egg-producing poultry known for their highly nutritious eggs and affordable price, making them popular among the general public. However, challenges in quail farming lie in feed efficiency and improving egg quality. One effort to address these challenges is the use of natural feed additives, such as moringa leaves (Moringa oleifera) and bilimbi fruit (Averrhoa bilimbi L.), which have potential as sources of natural antioxidants and bioactive compounds. This study aimed to evaluate the effects of moringa leaf powder supplementation in the feed, combined with bilimbi fruit extract in drinking water, on quail egg quality. The study used 180 female quails (Coturnix coturnix japonica) aged 20 weeks, in a feeding trial using a 2 × 3 factorial completely randomized design (CRD). The treatments consisted of two levels of moringa leaf powder (0% and 3%) and three levels of bilimbi extract (0%, 2.5%, and 5%), with three replications each. Observed parameters included egg weight, egg index, albumen index, yolk index, and Haugh Unit value. The analysis showed no significant interaction between moringa leaf and bilimbi extract supplementation on egg weight and egg index (P>0.05). These findings suggest that moringa leaf inclusion in feed has the potential to improve egg weight, although its effectiveness is influenced by dosage and interaction with other additives.